DEVELOPMENT OF STUDENT WORKSHEETS (LKPD) BASED ON A SCIENTIFIC APPROACH ASSISTED BY AMRITA OLABS VIRTUAL LABORATORY ON ELASTICITY MATERIAL AT SMAN 1 BILAH HULU - Simarmata, Maria Gracyiela P; Megalina, Yeni (UNIVERSITAS NEGERI MEDAN, 2022)
This development research aims to produce LKPD based on a scientific approach assisted by Amrita Olabs' virtual laboratory on elasticity material that is suitable for use in physics learning. This type of research is Research and Development (R & D) using Thiagarajan's 4D model which is limited to the development stage (Develop). The subjects in this study were material experts, media experts, teachers in the field of physics studies, and students of grade XI MIA 2 SMA Negeri 1 Bilah Hulu totaling 30 students. The instruments used in this study consisted of feasibility test questionnaires of material experts, and media experts, observation sheets, pretest, and posttest question instruments, and questionnaires of the responses of teachers in the field of study and students to LKPD based on a scientific approach assisted by Amrita Olabs' virtual laboratory. The results showed that LKPD based on a scientific approach assisted by the Amrita Olabs virtual laboratory developed was included in the category of very feasible to be used in the physics learning process based on the results of validation tests of material experts (92.85%) and media experts (93.18%). Teacher response to LKPD developed (98.21%) and student response (97.22%). Based on N-Gain calculations, LKPD based on a scientific approach assisted by Amrita Olabs virtual laboratory is in the medium category with a value of 0.69. With an average learning outcome of 79.50. Thus, it can be concluded that LKPD based on a scientific approach assisted by Amrita Olabs's virtual laboratory is feasible and effective to be used in physics learning.